Industria del petróleo, orden económico y orden político: estudio comparativo de Ghana y Guinea Ecuatorial - Ángeles Sánchez-Díez; Alicia Campos-Serrano (Revista Iberoamericana de Estudios de Desarrollo)
In this article, it is explored the conditioning elements of the economic and political dynamics surrounding the extraction of hydrocarbons in two countries in the Gulf of Guinea: Ghana and Equatorial Guinea. We will address the similarities and differences between both cases, based on the theoretical elements pointed out by the resource curse paradigm, a perspective that we will use critically. The differences in relation to the quantitative importance of oil resources with respect to total national income, regulatory development, transparency in the management of oil revenues and institutional quality are some of the most important divergences. However, these cases also present important similarities: in relation to the scarce role played by oil specialization in favouring regional insertion, as well as the great challenge of articulating productive linkages between the extractive industry and the local business network.